Dreamweaver CS3 for Windows and Macintosh - Negrino, Tom (Visual quickstart guide., 2007)
Takes readers step-by-step through the new features in Adobe Dreamweaver CS3, with new chapters on building dynamic pages with Ajax and Spry, and designing for mobile devices. Also covers improvements to using styles and CSS in Dreamweaver, and the new Browser Compatibility Check in Dreamweaver CS3. Beginning users will learn to create their first Web site, add text, style and position page content, manage styles, work with links, incorporate images, media, tables, forms, and frames, design site navigation, and more. Experienced users will find this a convenient reference to the new features of Dreamweaver CS3.--From publisher description.